Medicine & Philosophy. A Twenty-First Century Introduction - Johansson, Ingvar (De Gruyter, 2008)
This textbook introduces the reader to basic problems in the philosophy of science and ethics, mainly by means of examples from medicine. It is based on the conviction that philosophy, medical science, medical informatics, and medical ethics are overlapping disciplines. It claims that the philosophical lessons to learn from the twentieth century are not that nature is a 'social construction' and that 'anything goes' with respect to methodological and moral rules. Instead, it claims that there is scientific knowledge, but that it is never completely secure; that there are norms, but that they are situation-bound; and that, therefore, it makes good sense to search for scientific truths and try to act in a morally decent way. Using philosophical catchwords, the authors advocate 'fallibilism' and 'particularism'; a combination that might be called 'pragmatic realism'.